Characterization of antixenosis to Dichelops melacanthus (Hemiptera:Pentatomidae) in soybean genotypes - Canassa, Vinicius Fernandes [UNESP] (2017)
Soybeans are of great importance in the world agricultural landscape, and their productive potential is significantly reduced by attacks from insect pests. Factors such as the expansion of national agricultural regions, together with no-tillage management and off-season maize cultivation, have favored the increase of secondary species such as Dichelops melacanthus (Dallas) (Hemiptera: Pentatomidae), intensifying the damage caused by the soybean stink bug complex. The use of resistant genotypes may be a valuable strategy as an alternative to the excessive use of chemical control in crops. This study evaluated the attractiveness and feeding preferences of the green-belly stink bug in 17 soybean genotypes in different maturity groups (early, semiearly, and late) to characterize the expression of antixenosis resistance. To this end, free-choice tests of attractiveness and food preference were performed under laboratory conditions. The early genotypes PI 171451 and D 75-10169, the semiearly genotypes IAC 78-2318, IAC 100, IAC 74-2832, PI 227687, and IAC 24 and the late genotypes PI 274454, PI 274453, and L 1-1-01 expressed significant levels of antixenosis against adult D. melacanthus. These results will be useful for soybean breeding programs focusing on the stink bug resistance complex.